Security of Regional Economic Space: Conceptual Framework and System of Indicators - Sigov, Victor Ivglafovich; Pesotskiy, Andrey Alekseevich (Economy of Regions, 2017)
The purpose of the article is to develop the conceptual framework for the regional economic space security on the basis of the authors’ method of cyclic gradation. The subjects of the Russian Federation are considered as regions. The research attempts several objectives. The first one is to reveal the specificity of both the economic security in the conditions of the existing geo-economic tensions and import substitution policy initiated in 2014 and. Secondly, this study seeks to consider the relevant approaches to the analysis of regional economic security. Thirdly, we aimed at substantiating the spatial specificity of economic security at the regional level. And last, we suggest the method of cyclic gradation for the analysis of economic space security. The subjects of the Russian Federation face their own conceptual problems and challenges. One of these challenges is the increasing scale of integration processes. This situation is due to the asymmetric development of the Russian regions. In particular, the concentration of business activity in Moscow and several other subjects of Russian Federation, which are formally or informally recognized as strategic regions for the country development, demonstrates this asymmetry. The assessment of the economic security of Russian regions is conditioned by some methodological problems. In fact, the monitoring of socio-economic situation at the regional level does not consider the entire range of economic relations between business entities (companies). To develop the tools for the analysis of economic security at the regional level, the authors suggest to use in the system of monitoring such indicators as the average size of economic space, the quality of economic space, the intensity of economic space, the information availability, and the level of synchronization of economic time.